Formulation and Evaluation of Gliclazide Solid Dispersions Incorporated Tablets for Controlled Drug Release (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The current study deals with formulation and evaluation of gliclazide solid dispersion with HP β Cyclodextrin to enhance solubility and incorporate into tablet formulation for controlled release of gliclazide. Gliclazide solid dispersion (SD) prepared using varying ratios of HP β Cyclodextrin and evaluated. The optimized SD formulation incorporated into tablet by using hydroxypropyl cellulose, HPMC K 100M. The drug dissolution from tablet formulation analyzed and characterize. The formulation SD3 comprising of drug and polymer in 1:3 ratio displayed 43-fold increase in solubility when compared to pure drug. The formulation SD13 displayed maximum yield of 98.96% and maximum drug content of 99% chosen optimal for tablet formulation. FTIR studies revealed that there is no incompatibility between drug and polymers found. XRD studies revealed that the optimized solid dispersion formulation was found to be in amorphous state. Around 15 formulations of controlled release tablet blends evaluated for micrometric properties show that all the formulations posses’ good flow properties. Formulation F15 with maximum drug content of 99.99% and drug release of 99.96 % over 16h was chosen optimal and characterized. The release kinetics suggest that drug release followed zero order and release from tablets was anomalous non- fickian diffusion super case II transport. The results show that combination of solid dispersion and application of hydrophilic and hydrophobic polymers in matrix formation can facilitate better dissolution and absorption profile with greater patient compliance.